Evaluation of First-line and High-altitude Alpine Therapies for Patients with Immune Thrombocytopenia - Damineni, Ujwala (Asian Journal of Pharmaceutics (AJP), 2024)
Introduction: Acquired thrombocytopenia is a condition that causes immune thrombocytopenia (ITP) and is characterized by a platelet count of 100 × 109/l. The main challenges faced by Kyrgyz patients with ITP include the lack of clearly defined therapeutic regimens, high rate of complications associated with glucocorticoid use, unpredictability in treatment outcomes, and limited access to novel drugs. We aimed to evaluate the safety and efficacy of initial and supplementary treatments for individuals with ITP. Methods: Between 2015 and 2022, data from two sites in Kyrgyzstan, one in the country’s south and the other in the Republic, were retrospectively analyzed for 172 patients who met the inclusion criteria. The initial treatment regimen followed the current standards, consisting of several injection courses with a dose ranging from 0.4 to 1 g/kg over one to five doses. In addition, dexamethasone was delivered at a dosage of 40 mg orally or intravenously every day for 4 days, along with prednisone at a daily dosage of 1–40 mg for up to 4 weeks. Results: Only 22.4% of patients showed clinical and hematological improvement with prednisone treatment, and no partial or complete remission was observed. Of 91 patients, 57 (62.6%) experienced adverse events due to prednisone. The most common adverse events were hyperglycemia and metabolism (34.1%), followed by mental disorders (27.5%), sleeplessness (23.1%), hypertension (15.4%), and skin disorders (12.1%). Conclusion: In 45.4–77.6% of cases, conservative treatment approaches can effectively treat adult ITP patients. Current treatments include prednisone, dexamethasone, and the combined use of intravenous immunoglobulin, rituximab, and azathioprine.